Laboratory procedures for veterinary technicians - Sirois, Margi; Sirois, Margi (U.S Elsevier Ltd, 2020)
This procedures guide for veterinary technicians provides step-by-step coverage of the most widely used laboratory workups for microbiology, hematology, immunology, urinalysis, parasitology, and cytology.--From publisher description.
Keywords: Veterinary medicine -- Laboratory manuals; Veterinary clinical pathology -- Laboratory manuals; Clinical Laboratory Techniques -- veterinary; Animal Technicians; Pathology, Veterinary; Veterinary Medicine; Veterinary clinical pathology; Veterinary medicine